The student youth’s universal values and the Russian society development - I. P. Ryazantsev (RUDN journal of Sociology, 2021)
In recent decades, the concept of sustainable development has become the key theoretical focus for most countries. Traditions and values play an important role in ensuring sustainable development, including the attitudes of the younger generation, especially of the student youth who plan their professional future in Russia or abroad. The student youth preferences largely determine the country's development strategy and the assessment of its human capital. In 2018, the authors conducted the second wave of the empirical study Spiritual-moral culture of the Russian university (first wave - in 2012) which focused on the values of students of such leading universities as the Lomonosov Moscow State University and Saint Petersburg State University, and of such regional universities as the Tyumen State University, Samara State Technical University and Sevastopol State University. The research was conducted by a mass survey of 2505 students, including an online questionnaire. The concept of traditionalist modernization was used as an explanatory model. The article presents the results of the factor analysis of students value orientations according to the Schwartz scale and of students leisure practices, and also such indicators as authority, responsibility and tolerance of students. The authors come to the conclusion about the youths universal values that are quite flexible in relation to both modernization and preservation of the Russian specifics, which is somewhat different from the 2012 study with a more evident commitment to traditionalism. The authors interpret this fact as a generational feature of people born in the prosperous 2000s, which proves the gradual transition of the Russian society to the universal values, a combination of different value foundations and a departure from paternalistic attitudes. The article presents the results of the comparative analysis of some priorities of metropolitan and regional universities students, identifies the specifics of both types of universities, which allows to stress the different degrees of values universalism.